2020
DOI: 10.2174/0929867326666190506120213
|View full text |Cite
|
Sign up to set email alerts
|

Brain Cancer-Activated Microglia: A Potential Role for Sphingolipids

Abstract: : Almost no neurological disease exists without microglial activation. Microglia has exert a pivotal role in the maintenance of the central nervous system and its response to external and internal insults. Microglia have traditionally been classified as, in the healthy central nervous system, “resting”, with branched morphology system and, as a response to disease, “activated”, with amoeboid morphology; as a response to diseases but this distinction is now outmoded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 168 publications
(185 reference statements)
0
4
0
Order By: Relevance
“…[38] Various molecules of this pathway play roles ranging from activation to suppression in the pathogenesis of glioblastoma. [39] In our study, phytosphingosine has been demonstrated to induce the autophagy of glioma. [40] Ceramide and sphingomyelin can promote apoptosis of glioma, [41,42] while galabiosylceramide has the potential to participate in killing glioma cells by dendritic and natural killer cells.…”
Section: Discussionmentioning
confidence: 70%
“…[38] Various molecules of this pathway play roles ranging from activation to suppression in the pathogenesis of glioblastoma. [39] In our study, phytosphingosine has been demonstrated to induce the autophagy of glioma. [40] Ceramide and sphingomyelin can promote apoptosis of glioma, [41,42] while galabiosylceramide has the potential to participate in killing glioma cells by dendritic and natural killer cells.…”
Section: Discussionmentioning
confidence: 70%
“…Sphingolipids are structural compounds of biological membranes, and recent studies suggest sphingolipids can also serve as secondary messengers, participating in apoptosis, proliferation, senescence, angiogenesis, and vesicular trafficking [39,40]. Because alterations in bioactive sphingolipids have been linked to cancer progression and prognosis, their key metabolic enzymes have been actively pursued as novel targets in cancer drug development [41][42][43][44]. The enrichment analysis showed that SPTSSA is related to the oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Acting as a "double-edged sword," microglia play a pivotal role in maintaining tissue homeostasis while partially promoting neurological disease development when exposed to external and internal insults (36,48,49). A release of diverse nucleotides accompanies nerve injury, and some of these nucleotides act as "find/eat-me" signals in mediating neuron-glial interplay (46).…”
Section: Microglia and Neurons Coordinate Cns Homeostasismentioning
confidence: 99%